Development of a novel RO-PRO for intermittent renewable energy storage at grid scale - Tan, Qijia (Nanyang Technological University, 2022)
This study investigates the energy storage and production performance of the osmotic ESS integrating RO and PRO. Mathematical models were derived to graphically illustrate specific energy consumption, storage, production, and efficiencies under ideal conditions. The practical performance of the RO-PRO energy storage system is also assessed and compared to the modelled analysis to evaluate the negative effects of inefficiencies.